Evaluating a Parenting Program Using the CIPP Model: Evidence from a Kindergarten Laboratory School in Indonesia - Dian Wahyuningsih; Küçükoğlu, Adnan; Fransiska; Taşğın, Adnan (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
This study uses the Context, Input, Process, Product (CIPP) evaluation model to evaluate a parenting program implemented in a kindergarten laboratory school in Indonesia. Drawing on qualitative interviews with teachers, parents, and student interns, along with document analysis, the study investigates how the program addressed contextual needs, resource allocation, delivery mechanisms, and perceived outcomes. Data were collected through semi-structured interviews and supporting documents, then analyzed using thematic analysis to ensure systematic interpretation across CIPP components. The findings indiate that while the program was well-aligned with parental needs and supported by institutional resources, it faced participation rates, feedback mechanisms, and content inclusivity challenges. Parents reported improved confidence, communication skills, and understanding of child development as key benefits. However, the lack of systematic monitoring and follow-up limited the program’s sustainability. This study is essential as it provides a structured framework to assess parenting interventions’ quality and long-term viability in under-researched educational settings. It underscores the importance of participatory delivery methods, culturally sensitive materials, and integrated evaluation processes to enhance the long-term effectiveness of family engagement initiatives. Recommendations include embedding continuous feedback loops, involving diverse facilitators, and aligning program design with national goals on early childhood education and parental empowerment.